UNDERSTANDING PHILOSOPHY IN CONCEPTS KNOWLEDGE - Novialdi Novi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2024)
The philosophy of science clarifies the existence of science with other sciences which require knowledge as a medium of thinking and a means of scientific communication. These are language, mathematical logic, statistics and other data analysis techniques. The specifications and independence of science are faced with the increasing number of problems that science cannot answer. therefore, philosophy emerged as the answer. Philosophy provides explanations or answers to substantial and radical problems, while science continues to develop itself within its limits, while still being radically criticized, processes or interactions are basically the field of philosophy of science, therefore, philosophy of science can be placed as an effort to bridge the gap. between philosophy and science, so that science does not hate philosophy and philosophy does not hate science as a shallow understanding of nature. Reality is